Global Community Perceptions on Handling and Prevention COVID-19 on Decisions for Tourism Travel Visits to Indonesia - Sulian Ekomila; Nina Novira; Noviy Hasanah (Universitas Negeri Medan, 2022)
This paper is the result of research that aims to describe the global community's perception of the handling and prevention of Covid-19 in Indonesia regarding their plans and decisions to travel and visit Indonesia. Using a qualitative descriptive method approach, data were collected using a questionnaire on the Google Form® platform, distributed to informants in various countries using social media. After WHO (March 2020) declared a pandemic, it also had a tremendous impact on the tourism sector due to travel restrictions between countries and regions. The results of the study show that information from various sources shapes the perception of the global community about the handling and prevention of Covid-19 in Indonesia is bad. This affects the decision to travel and visit tourism to Indonesia. Informants are more concerned with physical comfort and health, related to these decisions during the pandemic. In conclusion, information from trusted sources or hoaxes will affect the global community's perception of the handling and prevention of Covid-19 in Indonesia, as well as interest and decisions to travel and visit Indonesia.